Review on heterogeneous photocatalytic disinfection of waterborne, airborne, and foodborne viruses: Can we win against pathogenic viruses? - Habibi-Yangjeh, Aziz; Asadzadeh-Khaneghah, Soheila; Feizpoor, Solmaz; Rouhi, Afsar (Journal of colloid and interface science, 2020)
[Display omitted] •Photocatalytic disinfection of waterborne, airborne, and foodborne viruses were reviewed.•Promising potential of heterogeneous photocatalysis for viral disinfection were discussed.•Compatibility of photocatalytic disinfection method with sustainable development was discussed.•Future research headlines about photocatalytic disinfection of different viruses were highlighted. Microbial pathogenic contaminations have world widely represented a serious health hazard to humans. Viruses, as a member of microbial contaminants, seriously threaten human health due to their high environmental resistance, having small sizes, and causing an extensive range of diseases. Therefore, selecting an appropriate technology to remove viral contaminants from the air, water, and foods is of prominent significance. Traditional methods for viral disinfection have not proven to be highly practical and effective because they need high energy resources and operational expenses. In recent years, semiconductor-based photocatalysis has attracted more attention in the field of microorganism inactivation due to its outstanding performance and mild reaction conditions. Therefore, this review primarily concentrates on the recent development in viral inactivation/disinfection by heterogeneous photocatalysts. Moreover, the photocatalytic viral inactivation of waterborne, airborne, and foodborne viruses is discussed. Given the appealing merits of heterogeneous photocatalytic disinfection of viruses, there is no doubt that this technology will be an impressively active research field and a source of comfort and confidence to humans in battling against viruses.